Analisis Pengaruh Transaksi Uang Elektronik terhadap Tingkat Inflasi di Indonesia - Ruth Damayanti (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2021)
Increasingly advanced technology encourages people to make transactions using electronic money (e-money). Nowadays, more Indonesian people use electronic money in their dealings, which is proven by the increasing volume of electronic money transactions from year to year. Electronic cash is chosed because it is more practical in making transactions with traders. The rising use of electronic money can affect the money supply, which can affect the inflation rate. Several studies have stated the effect of electronic money on inflation. This study aims to determine the impact of the variable volume and nominal value of electronic money transactions (e-money) on the inflation rate in Indonesia from January 2016 to December 2020. The data used in this study are secondary data with the type of monthly time series taken from Bank Indonesia, Kementerian Perdagangan, and BPS (Badan Pusat Statistik). The analysis technique used is the ECM (Error Correction Model). The Error Correction Model in this study aims to identify long-term and short-term relationships that occur because of the cointegration between research variables and the relationship between variables that are not stationary. This study indicates that in the long term, the variables volume of e-money transactions and money supply (M2) have a significant effect on the inflation variable. In contrast, other macroeconomic variables (BI rate and nominal value of e-money transactions) has no significant impact. Meanwhile, the short-term regression model shows no variables that have a substantial effect on the inflation variable.